2017
DOI: 10.1530/rep-17-0330
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of IFNT expression

Abstract: Summary Once interferon-tau (IFNT) had been identified as a Type I IFN in sheep and cattle and its functions characterized, numerous studies were conducted to elucidate transcriptional regulation of this gene family. Transfection studies performed largely with human choriocarcinoma cell lines identified regulatory regions of the IFNT gene that appeared responsible for trophoblast-specific expression. The key finding was the recognition that the transcription factor ETS2 bound to a proximal region within the 5/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…Our results have shown that HS during oocyte maturation, fertilization and/or embryo Trophoblastic cells produce IFNT, which is essential for maternal recognition of pregnancy (Spencer, Johnson, Bazer, & Burghardt, 2004), it is also a good marker for embryonic health (Roberts, Chen, Ezashi, & Walker, 2008). Another approach to investigate embryo/ trophoblast health is to evaluate caudal-type homeobox transcription factor (CDX2), which plays an essential role in trophoblast lineage emergence in ruminants (Ezashi & Imakawa, 2017). Therefore, the CDX2 antibody was used to assess trophoblastic cells on Day 7 embryos.…”
Section: Discussionmentioning
confidence: 92%
“…Our results have shown that HS during oocyte maturation, fertilization and/or embryo Trophoblastic cells produce IFNT, which is essential for maternal recognition of pregnancy (Spencer, Johnson, Bazer, & Burghardt, 2004), it is also a good marker for embryonic health (Roberts, Chen, Ezashi, & Walker, 2008). Another approach to investigate embryo/ trophoblast health is to evaluate caudal-type homeobox transcription factor (CDX2), which plays an essential role in trophoblast lineage emergence in ruminants (Ezashi & Imakawa, 2017). Therefore, the CDX2 antibody was used to assess trophoblastic cells on Day 7 embryos.…”
Section: Discussionmentioning
confidence: 92%
“…EZASHI;GHOSH;ROBERTS, 2001). A proteína Oct-4 mantida no TE pode suprimir a expressão de genes linhagem-específicos extra-embrionárias durante o desenvolvimento da pré-implantação e permitir a ploriferação extensiva do…”
unclassified
“…Instead, I came to the conclusion that the uniqueness of the IFNT system is in the highly conserved transcriptional control regions of its genes, which lack the virally inducible features of other type I IFN. Accordingly, I asked two pioneers in the IFNT field, Toshihiko Ezashi and Kazuhiko Imakawa to review what is currently known about the controls operating over transcription of IFNT in trophoblast (Ezashi & Imakawa 2017). Dr Imakawa was, of course, the first author on the 1987 Nature paper, while Dr Ezashi had described the ETS2/AP1/DLX3 enhancer element crucial in regulating IFNT gene expression (Roberts et al 2003).…”
mentioning
confidence: 99%